A Review of ESMAP Energy Efficiency Portfolio - World Bank (Washington, DC, 2014)
The summary reviews the Energy Sector Management Assistance Programme (ESMAP) activities in energy efficiency (EE), from 1997 to 2002, and evaluates thematic impacts, and lessons of the ESMAP Energy Efficiency Portfolio, though outputs such as capacity and knowledge, and other downstream activities, capturing best practices from lessons learned. It describes the overall impacts ESMAP played in mainstreaming EE within the Bank, and client countries, the catalytic role in supporting EE work, and its shift from its conventional demand-side management approach, to innovative energy service-driven, institutional and financing delivery mechanisms. Lessons suggest a careful topical selection for effective cross-country exchange, followed by systematic planning; establishing an institutional infrastructure for making energy conservation a profitable commercial business; establishing financing intermediaries between project developers and financiers, to bridge knowledge, and perception gaps, reducing transaction costs; and, expanding knowledge dissemination on innovative mechanisms, methodologies, and strategies in project design.